HOMESCHOOLING VERSUS PRIVATE SCHOOL - Rasulova Shahloxon; Muxtorova Xurshidaxon (Ta'lim innovatsiyasi va integratsiyasi, 2023)
In this article, the author aims at identifying key differences, strong and weak points of homeschooling and private school education in purpose of aiding parents to make a better decision.